(untitled) (Biological Sciences - PJSIR, 1996)
Milk-shakes especially containing apple are popular beverage of the summer season in Pakistan. Pineapple- flavoured apple milk-based beverages were prepared by using different do. es or four stabilizers and varying SMP contents. Arter one day’s cold storage, 16 formulations thus prepared were organoleptically evaluated by a trained panel of judges to select the best beverage. Recodan and Supercol applied @ 0.2-0.3% gave inferior-qual ity bever- ages, while Grindsted’s Gelodan and Givaudan’s stabilizer No. 76084-72 gave acceptable beverages. The best formu- lation wa. prepared by using 13% cane-sugar, 3% apple pulp, 2% SMP, 0.3% Givaudan’s stabilizer, 0.2% citric acid, 0.02% sodium citrate, 0.01 % potassium sorbate, 0.07% pineapple flavour, colour as desired and made volume to 100% with water. This was manufactured on a UHT plant by direct steam-injection technique at 144°C ancl packed in 250 ml brick packs. The results of the triangular taste test showed that the product was admired by the panelists and it remained good up to 75 days’ storage in ambient and 90 clays’ refrigerated storage.